L-Asparaginase of Leishmania donovani: Metabolic target and its role in Amphotericin B resistance. Issue 3 (December 2017) - Singh, Jasdeep; Khan, Mohd Imran; Singh Yadav, Shiv Pratap; Srivastava, Ankit; Sinha, Kislay K.; Ashish,; Das, Pradeep; Kundu, Bishwajit
Abstract: Emergence of Amphotericin B (AmB) resistant Leishmania donovani has posed major therapeutic challenge against the parasite. Consequently, combination therapy aimed at multiple molecular targets, based on proteome wise network analysis has been recommended. In this regard we had earlier identified and proposed L-asparaginase of Leishmania donovani (LdAI) as a crucial metabolic target. Here we report that both LdAI overexpressing axenic amastigote and promastigote forms of L. donovani survives better when challenged with AmB as compared to wild type strain. Conversely, qRT-PCR analysis showed an upregulation of LdAI in both forms upon AmB treatment. Our data demonstrates the importance of LdAI in imparting immediate protective response to the parasite upon AmB treatment. In the absence of structural and functional information, we modeled LdAI and validated its solution structure through small angle X-ray scattering (SAXS) analysis. We identified its specific inhibitors through ligand and structure-based approach and characterized their effects on enzymatic properties (Km, Vmax, Kcat ) of LdAI. We show that in presence of two of the inhibitors L1 and L2, the survival of L. donovani is compromised whereas overexpression of LdAI in these cells restores viability. Taken together, our results conclusively prove that LdAI is a crucial metabolic enzyme conferring early counter measure against AmB treatment by Leishmania . Graphical abstract: Image 1 Highlights: Role of L-asparaginase of Leishmania donovani in mediating early Amphotericin B resistance is proposed. Biochemical and biophysical characterisation of the enzyme is done. Proposed as metabolic target based on specific inhibition of this enzyme in parasites. Mechanistic insights into binding of inhibitors with the enzyme are detailed.